Alleviation of negative emotional and pain responses through amygdala-hypothalamic social circuit activation - Xinqi Lu; Guohua Chen; Weizhe Hong; Shuaishuai Hu; Rongfeng K. Hu (Proceedings of the National Academy of Sciences, 2025)
Pain is a multifaceted experience that not only impacts individuals physiologically but also reshapes their emotional well-being and social dynamics. The expression of pain and postpain emotional states is profoundly influenced by social contexts. Recent research has highlighted the pivotal role of social rewards—including empathy, support, and acceptance—in modulating both pain perception and subsequent negative emotional responses. However, how direct manipulation of brain circuits that govern social behaviors and social rewards impacts pain and negative emotional responses remains largely unexplored. Here, we investigated whether direct activation of a newly identified noncanonical social reward circuit—specifically, the projections from the medial amygdala (MeA) to the medial preoptic area (MPOA)—can mitigate pain-related emotional and behavioral responses. Our findings demonstrated that both optogenetic and chemogenetic activation of GABAergic neurons in the MeA significantly reduced freezing and anxiety-like behaviors after shock period as well as pain responses in the hotplate test in both male and female mice. Furthermore, optogenetic activation of the MeA-to-MPOA circuit produced similar behavioral outcomes. Together, our study expands the understanding of neural circuits underlying pain modulation and highlights the critical need to incorporate social and psychological factors into therapeutic approaches designed to improve human health and well-being.